PROSEDUR GADAI EMAS DIERA DIGITALISASI DENGAN AKAD QARDH PADA PT. BPRS AMANAH UMMAH KANTOR PUSAT LEUWILIANG - Marlina, Asti; Hanifan, Muhamad Zakie; Bimo, Widhi Ariyo (MONETER, 2021)
The gold pawn procedure in the digitalization era at PT. BPRS Amanah Ummah. In Indonesia, there is a dualism of sharia pawning institutions, namely in sharia pawnshops and sharia banking, sharia pawnshops serve objects other than gold and the like. While Islamic banks do not accept pledges other than gold, of course this does not escape using two transaction techniques, namely Qardh and Ijarah contracts. As for the mechanism of the sharia gold pawn procedure at PT. BPRS Amanah Ummah is a customer must and must come to the bank with gold to be pawned, then the bank checks or checks the quality of gold and gold content brought by the customer. As for how to pay installments or pay off debts to the bank, customers can make payments using digital methods such as ATMs, Mobile Banking, funds, OVO, and Link Aja. However, this cannot be separated from the transaction, which often encounters several problems, namely, the calculation of the estimated gold both for extension and at the time of repayment. Therefore PT. BPRS Amanah Ummah must develop an information system for the extension and repayment of the gold pawn. To develop a system of relations between tables (RAT), Entity Relationship Diagram (ERD), and Data Flow Diagrams (DFD) to see the flow of the system, while to build the flow of this system used system development tools Miscrosof Basic net and Myiso database. which will be used later..